(untitled) (Research, Society and Development, 2020)
Levan is an exopolysaccharide formed by fructose units produced by microorganisms during the fermentation of a culture medium containing sucrose, yeast extract and mineral salts. It is a biopolymer with industrial applications, both in the food area (color and flavor fixative, thickener and stabilizer of various foods) and also in the pharmaceutical (blood plasma substitute, immunomodulator, anticarcinogenic and hypocholesterolemic). This work aimed to specifically address aspects related to the design of levana production from the bacterium Zymomonas mobilis CCT 4494, varying the conditions of a submerged fermentation. The fermentation conditions for the production of levana were evaluated from a factorial planning and the response surface methodology was applied. The results demonstrate that the low p value found for the levan intercept (Y1), indicated that the levels studied in this research were well chosen and that the regression coefficient of the equation described the experiment with above 99% of confidence. Of the independent variables analyzed, agitation and its binary combination with temperature represented the most significant for this biopolymer biosynthesis. The highest production of levan obtained was 10.58 g.L-1, when using the initial sucrose concentration of 150 g.L-1. The values of biopolymer and biomass reduced significantly at temperatures above 30 °C and the fermentation product, such as the growth of Zymomonas mobilis CCT 4494, was proportional to the increase on concentration of sucrose tested.